A Research Synthesis of Therapeutic Interventions for Whiplash-Associated Disorder (WAD): Part 2 – Interventions for Acute WAD - Robert W Teasell; J Andrew McClure; David Walton; Jason Pretty; Katherine Salter; Matthew Meyer; Keith Sequeira; Barry Death (Pain Research and Management)
Whiplash-associated disorder (WAD) represents a significant public health problem, resulting in substantial social and economic costs throughout the industrialized world. While many treatments have been advocated for patients with WAD, scientific evidence supporting their effectiveness is often lacking. A systematic review was conducted to evaluate the strength of evidence associated with various WAD therapies. Multiple databases (including Web of Science, EMBASE and PubMed) were searched to identify all studies published from January 1980 through March 2009 that evaluated the effectiveness of any clearly defined treatment for acute (less than two weeks), subacute (two to 12 weeks) or chronic (more than 12 weeks) WAD. The present article, the second in a five-part series, evaluates the evidence for interventions initiated during the acute phase of WAD. Twenty-three studies that met the inclusion criteria were identified, 16 of which were randomized controlled trials with ‘fair’ overall methodological quality (median Physiotherapy Evidence Database score of 5.5). For the treatment of acute WAD, there was strong evidence to suggest that not only is immobilization with a soft collar ineffective, but it may actually impede recovery. Conversely, although exercise programs, active mobilization and advice to act as usual all appeared to improve recovery, it is not clear which of these interventions was the most effective. While there was also evidence supporting the use of pulsed electromagnetic field therapy and methylprednisolone infusion, the evidence was insufficient to establish the effectiveness of either of these treatments. Based on current evidence, activation-based therapy is recommended for the treatment of acute WAD; however, additional research is required to determine the relative effectiveness of various exercise/mobilization programs.